The Hepatitis C Virus NS4B Protein Can trans-Complement Viral RNA Replication and Modulates Production of Infectious Virus - Jones, Daniel M. (American Society for Microbiology (ASM), 2009)
Studies of the hepatitis C virus (HCV) life cycle have been aided by development of in vitro systems that enable replication of viral RNA and production of infectious virus. However, the functions of the individual proteins, especially those engaged in RNA replication, remain poorly understood. It is considered that NS4B, one of the replicase components, creates sites for genome synthesis, which appear as punctate foci at the endoplasmic reticulum (ER) membrane. In this study, a panel of mutations in NS4B was generated to gain deeper insight into its functions. Our analysis identified five mutants that were incapable of supporting RNA replication, three of which had defects in production of foci at the ER membrane. These mutants also influenced posttranslational modification and intracellular mobility of another replicase protein, NS5A, suggesting that such characteristics are linked to focus formation by NS4B. From previous studies, NS4B could not be trans-complemented in replication assays. Using the mutants that blocked RNA synthesis, defective NS4B expressed from two mutants could be rescued in trans-complementation replication assays by wild-type protein produced by a functional HCV replicon. Moreover, active replication could be reconstituted by combining replicons that were defective in NS4B and NS5A. The ability to restore replication from inactive replicons has implications for our understanding of the mechanisms that direct viral RNA synthesis. Finally, one of the NS4B mutations increased the yield of infectious virus by five- to sixfold. Hence, NS4B not only functions in RNA replication but also contributes to the processes engaged in virus assembly and release.